Effect of Corporate and Dividend Income Tax Rates on Bank Capital - Adrian Teja (Universitas Prasetiya Mulya, 2022)
The study uses quantitative method to estimate the effect of Corporate- and Dividend-Income-Tax rates on Total-Bank-Capital, Tier-1-Bank-Capital, and Tier-2-Bank-Capital ratios. The samples are banks from ASEAN-4 countries, i.e. Indonesia, Malaysia, The Philippines, and Thailand, taken in 2020. The effects of Corporate- and Dividend-Income-Tax on Total-Bank-Capital, Tier-1-Bank-Capital, and Tier-2-Bank-Capital ratios were analyzed using cross-section regression. We placed Total-Bank-Capital, Tier-1-Bank-Capital, and Tier-2-Bank-Capital ratios as the dependent variable. Corporate- and Dividend-Income-Tax rates were placed as the independent variable. Both Corporate- and Dividend-Income-Tax rates are statistically significant and positively affect the Total-Bank-Capital and Tier-1-Bank-Capital. The findings suggest that high Corporate- and Dividend-Income-Tax rates reduce banks' significant risks. Corporate-Income-Tax rates and negatively affect Tier-2-Bank-Capital. The finding suggests that lower tax rates will induce banks to increase their Tier-2-Bank-Capital ratio. However the effect of Dividend-Income-Tax rates on Tier-2-Bank-Capital is not statistically significant.